2007
DOI: 10.1007/s00198-007-0484-z
|View full text |Cite
|
Sign up to set email alerts
|

Association studies of ALOX5 and bone mineral density in healthy adults

Abstract: These data do not provide consistent evidence of association between genomic variation in ALOX5 and clinical variability in aBMD in healthy subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Spine and total hip BMD values were also entered into a logistic regression model to determine their influence on fracture risk. Computed regression residuals, representing covariate-adjusted study phenotypes, were used in subsequent analyses (30).…”
Section: Discussionmentioning
confidence: 99%
“…Spine and total hip BMD values were also entered into a logistic regression model to determine their influence on fracture risk. Computed regression residuals, representing covariate-adjusted study phenotypes, were used in subsequent analyses (30).…”
Section: Discussionmentioning
confidence: 99%
“…Spine, total hip, and radius BMD values were also entered into logistic regression model to determine their influence on fracture risk. Computed regression residuals, representing covariate-adjusted study phenotypes, were used in subsequent analyses (8). Association analyses were performed using the program PedGenie (18), statistical software developed for analyses of pedigrees and independent individuals, computing a statistic equivalent to ANOVA under three genetic models (additive, dominant, and recessive).…”
Section: Data Pre-processing and Statistical Analysismentioning
confidence: 99%
“…More than 200 candidate genes influencing the disease have already been reported (2,3), but the exact genetic background and the interactions among suspected genes as well as genes and environmental or lifestyle factors (4) are still poorly understood (5). Previous studies have also shown that genetic influences can differ among distinct populations and between genders (6)(7)(8). Bone mineral density (BMD) and risk of osteoporotic fracture, predominant study phenotypes in genetic studies, are affected by several genes and their polymorphisms.…”
Section: Introductionmentioning
confidence: 99%
“…Second, previous analyses indicated that there was no evidence of stratification in our sample; therefore, population stratification was unlikely to account for the significant associations found in our population sample. (23) Third, rather than testing only a few SNPs, we tested a range of SNPs that spanned from strong LD to no LD with the most significant The presence and absence of gene expression determined by RT-PCR are denoted by + and −, respectively. Weak, but detectable, amplification is denoted by (+).…”
Section: Discussionmentioning
confidence: 99%
“…(23) The program Haploview (19) was used to examine the extent of LD between the SNPs to ensure that the SNP density was sufficient to evaluate evidence of association. LD (DЈ statistic) was evaluated using one randomly selected individual in each family.…”
Section: Statistical Analysesmentioning
confidence: 99%